Supplier management in German manufacturing companies : An empirical investigation - Szwejczewski, Marek; Goffin, Keith; Lemke, Fred; Pfeiffer, Rolf; Lohmüller, Bertram (Emerald Group Publishing Limited, 2001)
A key issue for manufacturers is supplier management, i.e. organising the optimal flow of high quality, value-for-money materials or components from appropriate innovative suppliers. Many companies now recognise the central role that supplier management plays in achieving long-term competitive advantage. This paper presents the results of a study of supplier management practices in Germany, contrasted against those in the UK. It identifies a key difference – German manufacturers have not reduced their supplier base as much as the companies in the UK. However, it appears that German manufacturers will be reducing their supplier base in the near future, although they are likely to follow a policy of multiple sourcing rather than single-sourcing from suppliers. The results of the research have strong implications for German companies as they clearly indicate the potential for performance improvement through the adoption of best practices in the field of supplier managemen
Keywords: Germany; Manufacturing industry; Supply-chain management; Surveys; United Kingdom